PARTICIPATION OF STUDENTS IN THE QUALITY ASSURANCE SYSTEM - Д. Щеглюк (Київський національний університет імені Тараса Шевченка, 2018)
HEI should regulate and encourage active participation in the quality assurance of higher education of all stakeholders, as well as stimulate their interaction. The introduction and support of appropriate mechanisms to ensure the maximum participation of students at different levels of the quality assurance system is one of the main tasks of the leadership of departments, faculties and institutions of higher education. Student involvement in quality can have a positive influence on the delivery and development of any aspect of the student educational experience, whether implemented by the higher education provider, a faculty, a department, or an individual member of staff. It is necessary to envisage the involvement of students in all processes and quality assurance procedures at all institutional levels. It is necessary to clearly define the rights that are granted in each case to student self- government bodies and student. Students should be provided with methodological support to improve their participation in internal and external quality assurance processes. The selection of experts for accreditation processes from the number of students should be carried out through an open competition with the assistance of national student organizations.

На основі аналізу чинної нормативної бази з питань вищої освіти України, стандартів ISO серії 9000 та Стандартів і рекомендацій щодо забезпечення якості в Європейському просторі вищої освіти визначено основні інституційні рівні, на яких закладами вищої освіти має бути врегульована участь здобувачів освіти у системах забезпечення якості. Указано на необхідність взаємодії всіх стейкхолдерів у функціонуванні систем забезпечення якості вищої освіти. Запропоновано залучення здобувачів освіти до акредитації освітніх програм через процедури відкритого конкурсу.
УЧАСТЬ ЗДОБУВАЧІВ ВИЩОЇ ОСВІТИ У СИСТЕМІ ЗАБЕЗПЕЧЕННЯ ЯКОСТІ
Keywords: здобувачі освіти; забезпечення якості; система забезпечення якості; стандарти; інституційний рівень.; students; quality assurance; quality assurance system; standards; institutional level.